KAJIAN PRAGMATIK DALAM BAHASA ARAB (ANALISIS BENTUK DAN FUNGSI TINDAK TUTUR DIREKTIF BAHASA ARAB DALAM FILM â€œASHABUL KAHFIâ€) - Nurwendah, Yusti Dwi; Mahera, Intan Annisaul (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2019)
Pragmatics is the study of the context outside the language and the purpose of speech. This study focuses on one type of pragmatics, namely the speech act of Arabic directives in the film "Ashabul Kahfi". This research serves to describe the forms of directive speech acts and their functions in the film "Ashabul Kahfi". The method used in this study is descriptive analysis method, which is carried out through three stages, (1) the stage of data collection (2) the data analysis stage, and (3) the stage of presenting the results of data analysis. The results showed that the form of Arabic directive speech acts in the film "Ashabul Kahf" included direct speech acts, indirect speech acts with imperative sentence forms, indirect speech acts with declarative sentence forms and interrogative sentences characterized by question words, literal speech acts and non-literal speech acts. While the function of the Arabic directive speech act in the movie "Ashabul Kahfi" is Requestives directive speech act, directive speech act Questions, directive Requirements speech act, directive prohibitives speech act, directive act of Permissives directive, directive advisory act.